Nanostructure patterns on stainless-steel upon ultrafast laser ablation with circular polarization. (November 2018) - Lazzini, G.; Romoli, L.; Tantussi, F.; Fuso, F.
Highlights: Laser ablation of AISI 440 C stainless-steel with sub-ps pulses at 1552 nm. Comprehensive morphological analysis of samples processed with different parameters. Observation of ripple-like LIPSS despite the use of circular polarization. Occurrence of inclined surface and interpretation through differential absorption of polarization components. Abstract: Ripple-like nanostructure patterns are known to occur in ultrafast laser ablation with linearly polarized radiation. The observation of similar features at the bottom of grooves produced during laser ablation of stainless-steel with circular polarization is reported here. A comprehensive morphological analysis of the machined surfaces, carried out by electron and scanning probe microscopes, reveals a marked dependence of feature shape on process parameters, in particular on the scanning velocity of the laser spot. Such a dependence is interpreted based on the occurrence of an inclined surface during the ablation and on the consequent differential absorption of s- and p-polarized components of the laser radiation by stainless-steel. The resulting anisotropy of the absorbed energy mimics irradiation with elliptical polarization that can drive formation of ripple-like, elongated nanostructures.